The good, the bad, and the ugly of international debt market data - Nina Boyarchenko; Leonardo Elias (Federal Reserve Bank of New York, 2023)
Comprehensive granular data on firms' access to international credit markets and its determinants is instrumental in answering a wide set of questions in international macroeconomics and finance. We describe how to put together data on primary market issuance and secondary market pricing, how to track debt securities over their lifetimes on firms' balance sheets, and how to match bond-level information to financial statements of the ultimate corporate parents. We illustrate the importance of using comprehensive data on corporate bonds over their lifecycle by documenting a high propensity of early maturity, procyclicality of the propensity to prepay, and a resulting procyclicality of effective time-to-maturity.
Keywords: G15; 330; debt markets; corporate capital structure; bond spreads